(untitled) (Journal of Architectural Design, 2023)
The article is devoted to the opportunities that open up BIM technologies as a solution to some of the problems of the modern design and construction industry. Modern design technologies in the Republic of Uzbekistan and existing problems and shortcomings are discussed. Real-life examples of the factors that cause them are given. A specialist who carefully reads the article will conclude why our economy needs new technologies.